Volunteer Activity in the Context of Formation of Social Intellect of Future Specialists in Social Work - Tatsiana Sokolova (Vasyl Stefanyk Precarpathian National University, 2016)
The article describes such concepts as "social intellect" and "volunteer activity"; presents approaches to the definition of the phenomenon of volunteering. The author proves the possibilities of volunteer activity in the context of formation of social intellect of future specialists in social work, reveals the features of organization of students' practical volunteer activity to form their social intellect.